Distributions of lithium-ion and nickel-metal hydride battery elements in copper converting - Tirronen, T.; Sukhomlinov, D.; O'Brien, H.; Taskinen, P.; Lundström, M. (Journal of cleaner production, 2017)
Waste batteries, such as rechargeable Lithium-ion and Nickel-Metal Hydride batteries, are important secondary raw materials. They contain considerable amounts of valuable metals, like Ni, Co, Cu, Mn, rare earth elements (REE) and Li. Recovery of these metals from waste streams is vital to decrease the primary production, increase resource efficiency and mitigate against future supply risk. Especially, as the consumption of rechargeable batteries is estimated to rise significantly and the current recovery rates are extremely low. Pyrometallurgical processing, such as secondary copper smelting, offers potentially an effective recovery route for a number of the key elements. Based on the fact that different trace elements have characteristic thermodynamic properties, they distribute in different material streams during pyrometallurgical processing, i.e. metal, matte, slag, magnetite, with different ratios. In particular, solubilities of trace elements in the primary magnetite phase have been properly investigated for the first time. Furthermore, fundamental data about the distributions of Li, Mn, and REE's in copper processing are also subject of speculation. The present study ascertains the distributions and deportments of battery elements during copper converting, between temperatures 1200 and 1275 °C. The thermodynamic data measured as a part of this study will provide basics and solid guidelines for the recovery of the studied trace elements in the industrial copper smelting and converting processes. •We studied Li-ion and NiMH battery metals in the copper converting end-point.•We measured the distribution coefficient for the studied elements at 1200–1275 °C.•Dissolution of trace elements in solid magnetite was measured experimentally.•We determined Li, Mn and Nd distributions in copper processing for the first time.